Possibilities of Object-Oriented Programming in the Organisational Architecture of Firms - Martinez, Felipe (2013)
The procedures to establish organisational structure are the focal subject of this study. The review of literature and research components of this dissertation identify that there is lack of procedures, processes, and working guidelines to facilitate this managerial task. The creation of any of these procedures is inherently complex as is the intended organisational structure to create. Organisational theories present several models. They identify and discuss primary organisational elements but fail to propose adequate methods for structuration. The doctoral candidate confronts this void to both practitioners and academicians by means of two approaches. Firstly, it proposes a procedure to institute organisational structure founded on the Object-Oriented paradigm. Secondly, it compares and contrasts this procedure with existing processes deployed by managers, entrepreneurs, and expert-consultants. The presentation of this procedure includes a fundamental analogy for its creation; the paradigm selection and explanation (Object-Oriented); a detailled 'step by step' guide for successful implementation and concrete applications of the procedure. The review in this area is extensive and promotes analyses that are both practical as well as theoretical. This assessment promotes and develops a research based on organisational structuring experiences. It uses quantitative and qualitative tools to collect the data. The data are discrete. Various techniques are employed to illustrate findings. Bar graphs with distributions curves represent the data. The graphical and statistical analyses argue the existence of a general procedure to set up the organisational structure. In addition, the research compares the general and proposed procedures. It uses descriptive and graphical tools for the comparison. The findings corroborate the proposed procedure as a valid method to implement organisational structure.